Dimension of Debt to Earnings Management - Irine Mahardhika Putri; Tumirin Tumirin; Nyimas Wardatul Afiqoh (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Long Term Debt to Equity Ratio (LTDER) on earnings management. This study uses a quantitative research approach. Collecting techniques using documentary data or secondary data. The sample selection used purposive sampling method. From the predetermined criteria, a sample of 120 company data was obtained. The data analysis used multiple linear regression analysis. The results showed that the Debt to Equity Ratio had a significant positive effect on earnings management. Debt to Asset Ratio has a significant positive effect on earnings management. Long Term Debt to Equity Ratio has a negative effect on earnings management. Simultaneously variable Debt to Equity Ratio, Debt to Asset Ratio, and Long Term Debt to Equity Ratio has a negative effect on earning management. Simultaneous significant test using by comparing F count with F table.